2018
DOI: 10.1002/cne.24575
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between neuronal birthdates and tonotopic positions in the mouse cochlear nucleus

Abstract: Tonotopy is a key anatomical feature of the vertebrate auditory system, but little is known about the mechanisms underlying its development. Since date of birth of a neuron correlates with tonotopic position in the cochlea, we investigated if it also correlates with tonotopic position in the cochlear nucleus (CN). In the cochlea, spiral ganglion neurons are organized in a basal to apical progression along the length of the cochlea based on birthdates, with neurons in the base (responding to high-frequency soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The cochlear sensory domain is comprised of a single row of IHCs and three rows of OHCs, which are innervated by type I and II SGNs respectively. Morphologically, the SGNs are bipolar: they extend peripheral axons (sometimes termed "dendrites") that innervate hair cells, and central axons that project out of the inner ear and innervate neurons within the cochlear nucleus (Nayagam et al, 2011;Shepard et al, 2019). Figure 1A-C shows wholemount or cross-sectional views of these structures with the SGNs labeled with anti-NF200 antibodies and the hair cells labeled with anti-MyoVI antibodies.…”
Section: Differentiating Hair Cells Express Sema5b Whereas Sgns Exprmentioning
confidence: 99%
“…The cochlear sensory domain is comprised of a single row of IHCs and three rows of OHCs, which are innervated by type I and II SGNs respectively. Morphologically, the SGNs are bipolar: they extend peripheral axons (sometimes termed "dendrites") that innervate hair cells, and central axons that project out of the inner ear and innervate neurons within the cochlear nucleus (Nayagam et al, 2011;Shepard et al, 2019). Figure 1A-C shows wholemount or cross-sectional views of these structures with the SGNs labeled with anti-NF200 antibodies and the hair cells labeled with anti-MyoVI antibodies.…”
Section: Differentiating Hair Cells Express Sema5b Whereas Sgns Exprmentioning
confidence: 99%
“…A, anterior; D, dorsal; L, lateral; M, medial; N, nasal; P, posterior; T, temporal; V, ventral. Modified after 12, 41, 5358.…”
Section: Molecular Odorant Mapmentioning
confidence: 99%
“…Migration within the alar plate, as in the spinal cord 179 , suggests that more sophisticated pulse-chase experiments with modern EdU/BrdU double labeling are needed to resolve temporal maps. Indeed, a very recent article showed that the anterior parts of the cochlear nucleus complex show a coordinated cell cycle exit matching that of spiral ganglion neurons 58 . The temporal progression of spiral ganglion cell cycle exit 57, 120 and progressive development of spiral ganglion neurons and their central projections 121 imply a birth-dating bias toward map formation ( Figure 1C and Figure 2B).…”
Section: Overview Of Brainstem Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing cochlea, the central processes of ANFs innervate the CN in a developmental gradient according to tonotopy 5 . In mice, SGNs are born in a basal to apical progression along the length of the cochlea, with neurons in the base (future high-frequency preference) born early around mouse embryonic day (E) 9.5-10.5 and those in the apex (future low-frequency preference) born later, around E12.5 to 13.5 [6][7][8][9] . This sequential neurogenesis of SGNs results in ANFs from the early-born basal SGNs initiating outgrowth about 2-3 days earlier than ANFs from the late-born apical SGNs.…”
Section: Introductionmentioning
confidence: 99%